2000
DOI: 10.1002/(sici)1526-4998(200005)56:5<413::aid-ps140>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of methyl iodide and synergy with chloropicrin for control of fungi

Abstract: Efficacy of soil fumigation with methyl bromide and methyl iodide against Botrytis cinerea, Colletotrichum gloeosporioides, Fusarium oxysporum, Gliocladium virens, Phytophthora citricola, Phytophthora citrophthora, Pythium ultimum, Rhizoctonia solani and Verticillium dahliae was determined in laboratory experiments in closed fumigation chambers. Pythium ultimum was the most sensitive fungal species with EC50 values for methyl bromide and methyl iodide of 15.5 and 8.6 µM, respectively. R solani was the least se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 23 publications
(34 reference statements)
4
43
0
Order By: Relevance
“…Iodomethane (Midas) can be as effective as MeBr, and it is not as likely to deplete ozone because Midas is photolyzed before it reaches the stratosphere (Solomon et al, 1994). The dilution of Midas with CP can decrease costs for this fumigant and increase efficacy due to synergy with CP (Hutchinson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Iodomethane (Midas) can be as effective as MeBr, and it is not as likely to deplete ozone because Midas is photolyzed before it reaches the stratosphere (Solomon et al, 1994). The dilution of Midas with CP can decrease costs for this fumigant and increase efficacy due to synergy with CP (Hutchinson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The largest slope at the inflection point of the curve (b value) indicated that F. oxysporum and R. solani have greater susceptibility to pure MI (MI:Pic, 98:2) than to the other fumigants (table 2). Early doseresponse studies evaluated the efficacy of pure MI and MBr to control a range of soilborne pathogens and found P. ultimum to be the most sensitive and R. solani to be the least sensitive (Hutchinson et al 2000;Ohr et al 1996), and only partial mortality of F. oxysporum and V. dahliae was achieved with these fumigants. Other studies have reported that MI and MBr controlled nematodes, including citrus nematode (Becker et al 1998;Hutchinson et al 1999;Luo et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most MBr efficacy studies have assessed the dose response using pure MBr (98%) and found this compound very effective against a wide range of pests; however, the analog compound, MI, was found to be as effective as or more effective than MBr (Becker et al 1998;Hutchinson et al 1999;Hutchinson et al 2000;Ohr et al 1996;Zhang et al 1997). In this study, the mixed fumigants MBr:Pic (50:50) and MI:Pic (50:50) both controlled T. semipenetrans, P. ultimum and F. oxysporum, but MI:Pic was more effective in controlling R. solani compared to MBr:Pic (tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations